Pengelolaan Sekolah Yang Baik Dan Strategi Pembelajaran Aktif - Febriansyah Febriansyah; Didin Hikmah Perkasa; Wilhelmus Agung Dopo (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2023)
The superior school assessment model is an instrument that is expected to be used by education managers to determine the level of success of each school. The results of this assessment can then be used as material for consideration in making efforts to improve the school. Schools that have a good management system, are transparent and accountable, and are able to empower every important component of the school, both internally and externally, in order to achieve the school's vision-mission-goals in a superior and efficient manner. The concept of a superior school is a school that is able to optimize all inputs and processes for achieving educational output, namely school achievement, especially student achievement which is marked by having all the abilities in the form of competencies required in learning. The characteristics of superior schools are: 1) the leadership of the principal is strong. 2) high expectations for student achievement, 3) emphasis on basic skills, and 4) orderly and controlled atmosphere. Superior school leadership by the principal because the principal is a figure in realizing the vision, mission and goals of the school, namely an excellent and efficient school.